OUTCOME OF SMALL FRAGMENT DCP FOR FRACTURE OF RADIUS & ULNA IN ADULTS - Muhammad Kaleem Shaukat; Asim Rasool; Javed Iqbal Awan; Osama Jaffar; Muhammad Junaid Naqeed (Journal of University Medical & Dental College, 2020)
ABSTRACT: INTRODUCTION: Diaphyseal fractures of radius and ulna are common orthopedic injuries 1. They can cause significant loss of function if inadequately treated 2.The goal of treatment is good bone healing with preservation of upper limb function 2,3. Both operative and non operativetan treatment methods are available but operative treatment with small fragment dynamic compression plate fixation is recognized as treatment of choice for these fractures 4. Non union is a major Complication of this procedures 5, which can be disabling as it affects not only the forearm but also the elbow and wrist 6. OBJECTIVE: To determine the outcome of Small Fragment Dynamic Compression plate fixation for Diaphyseal fractures of radius and ulna in adults on the basis of frequency of union and non union. STUDY DESIGN: Descriptive case series. SETTINGS: Orthopedic Department Allied Hospital, Faisalabad, Madina Teaching Hospital, Faisalabad. RESULTS: 97 patients (76 males, and 21 females) with a mean age of 30.86+/-10.30 years were operated for small fragment dynamic compression plate fixation between June 2010 and May 2011. Out of the total 97 patients, 90 (92.8%) patients showed union while 07( 7.2%) patients showed non union. Outcome in terms of union was excellent in 63 (64.9%) patients, good in 27 (27.8%) and poor in 7( 7.3%) patients. CONCLUSION: The small fragment dynamic compression plate fixation is the treatment of choice for Diaphyseal fractures of radius and ulna in adults. Non union is an important Complication of this procedure and needs to be evaluated.